Asymptotic Equivalence of Triangular Differential Equations in Hilbert Spaces - Dang, Dinh Chau; Vu, Tuan (Ukrains’kyi Matematychnyi Zhurnal, 2005)
In this article, we study conditions for the asymptotic equivalence of differential equations in Hilbert spaces. We also discuss the relationship between the properties of solutions of differential equations of triangular form and those of truncated differential equations.